Post-mortem assessment of vimentin expression as a biomarker for renal tubular regeneration following acute kidney injury - Juan Carlos Alvarez Moreno; Hisham F. Bahmad; Christopher A. Febres-Aldana; Andrés Pirela; Andres Azuero; Ali Salami; Robert Poppiti (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Background Acute kidney injury (AKI) is a common cause of morbidity and mortality. It mainly targets the renal tubular epithelium with pathological changes, referred to as acute tubular injury. The latter is followed by a regenerative response that is difficult to visualize on routine hematoxylin and eosin (H&E) stains. In this study, we examined the regenerative capacity of renal tubules by correlating vimentin (VIM) immunohistochemical (IHC) expression and pathological findings of AKI and renal tubular regeneration (RTR) on H&E. Methods We reviewed 23 autopsies performed in the clinical setting of AKI and RTR. VIM expression was scored in the renal cortical tubular epithelium using a statistical cutoff ≥ 3% for high expression and < 3% for low expression. Results Of the 23 kidney tissues examined, seven (30.4%) had low VIM expression, and 16 (69.6%) had high VIM expression. Kidney tissues with evidence of AKI and RTR had significantly higher VIM expression. Renal peritubular microenvironment features showing regenerative changes on H&E were associated with high VIM expression. In the univariate model, kidney tissues with RTR were 18-fold more likely to have high VIM expression. Conclusions In conclusion, our findings suggest that VIM could serve as an IHC marker for RTR following AKI. However, correlation with H&E findings remains critical to excluding chronic tubular damage. Collectively, our preliminary results pave the way for future studies including a larger sample size to validate the use of VIM as a reliable biomarker for RTR.